Microfinance and poverty reduction in Tanzania : experiences from Dar es Salaam - Khoda, Sher (2011)
The emergence of micro credit as an effective tool for poverty reduction is widely recognized in the world since the 1990s. The World Bank also values categorically micro credit for poverty alleviation. The financial sector reform in Tanzania in 1991 emphasized the need for micro credit to the poor, in order to enable them to become entrepreneurs. It also aimed at providing household support as a mean of poverty reduction and economic growth. However, a number of constraints exist within this reform, for instance, establishing a new micro finance organization and providing credit access to poor. Therefore entrepreneurship and household income situation is not improving as it is expected by the micro finance organizations. This study aims to focus on the value of micro credit for poverty reduction and at the same time the challenges micro finance organizations face in realizing their objectives. This research is qualitative in nature followed by case study method. The data was collected from micro credit clients in Der es Salaam, Tanzania.